The dynamic effect of electric charge on a conductor - V. I. Gorbunkov; M. A. Kholmov; A. V. Iukina; I. V. Ksendzov; V. A. Zhigadlo (Омский научный вестник)
An estimate of the dynamic effect the electric fields of a charged sphere on a current-carrying conductor is obtained. The characteristic time parameter of charge transfer to a conducting sphere, as well as the momentum Conservation Principle are applied. The found values of the interaction force and the transmitted energy can make it possible to determine the physical nature of the dynamic effect. A description of the laboratory setup is presented.